ASSOCIATION OF SERUM FERRITIN AND VITAMIN D₃ WITH TYPE 2 DIABETES MELLITUS: A CASE-CONTROL STUDY IN KIRKUK CITY, IRAQ - Mahdi, Iman Noori Mahmood (Journal for Technology and Science, 2026)
Objective: Objective: Type 2 diabetes mellitus (T2DM) is a growing problem around the world, and Iraq is no exception—more people are being diagnosed with it every year. Researchers have started to notice that changes in certain blood markers, like ferritin and vitamin D₃, might play a role in diabetes risk. But so far, there hasn't been much data on how these markers behave in people from Kirkuk. Methods: A total of 100 subjects were enrolled, comprising 50 diagnosed T2DM patients and 50 age- and sex-matched healthy controls from Kirkuk General Hospital. Fasting blood samples were collected to measure serum ferritin and Vitamin D₃ levels using ELISA. Statistical analyses included independent t-tests to compare means, Pearson's correlation to examine relationships between variables, and binary logistic regression to identify significant predictors of T2DM. Results: The study found that T2DM patients had significantly higher mean serum ferritin levels (182.4 ± 48.6 ng/mL) compared to controls (78.5 ± 22.1 ng/mL; p < 0.001). Conversely, mean serum Vitamin D₃ levels were significantly lower in T2DM patients (15.8 ± 4.2 ng/mL) than in controls (38.6 ± 10.5 ng/mL; p < 0.001). A significant negative correlation was observed between ferritin and Vitamin D₃ levels in the patient group (r = -0.562, p < 0.001). Logistic regression identified elevated ferritin (OR = 1.082, p < 0.001) and decreased Vitamin D₃ (OR = 0.821, p < 0.001) as significant independent predictors of T2DM. Novelty: This study demonstrates a strong association between elevated serum ferritin, Vitamin D₃ deficiency, and the presence of T2DM in the Kirkuk population. These biomarkers could serve as valuable diagnostic and prognostic tools. Further longitudinal studies are warranted to establish causality and explore the underlying mechanisms.